Changes over time in echocardiographic variables and atrial electromechanical intervals after ablation for atrial fibrillation. Issue 6 (18th March 2014) - Mano, Hiroaki; Okumura, Yasuo; Watanabe, Ichiro; Ohta, Masakatsu; Kogawa, Rikitake; Sasaki, Naoko; Nakai, Toshiko; Ohkubo, Kimie; Kofune, Masayoshi; Nagashima, Koichi; Sonoda, Kazumasa; Haruta, Hironori; et al.
Abstract: Introduction: Acute and mid‐term effects of ablation for atrial fibrillation (AF) on left atrial (LA) and left ventricular (LV) function and the atrial electromechanical interval are controversial. Methods: Echocardiographic variables and the PA‐TDI interval (time from ECG lead II P‐wave onset to lateral a′ wave on tissue Doppler tracings, indicating the total atrial conduction time [TACT]) were evaluated in 33 paroxysmal AF patients before, 1 day, and 3, 6, and 12 months after ablation. Results: During a 12‐month follow‐up, 10 (30.3%) patients had recurrent AF, associated with a greater baseline LA volume (LAV) (48.4±19.3 mm 3 vs. 38.7±11.4 mm 3, P =0.0811) and PA‐TDI interval (163.9±11.0 ms vs. 151.1±14.6 ms, P =0.0189) than in patients without AF recurrence. By 6 months after ablation, LAV had decreased progressively in the non‐recurrence group (27.9±8.1 mm 3, P <0.0001 vs. baseline), but the decrease was modestly significant in the recurrence group (36.3±7.5 cm 3, P =0.0380). LV ejection fraction (LVEF) modestly increased 1 day after ablation in both groups and remained unchanged in the non‐recurrence group (67.9±8.1% at baseline to 70.5±5.9% at 12 months, P =0.1711), whereas it decreased gradually below the baseline value in the recurrence group (68.2±11.3% to 60.9±13.6%, P =0.1025). The PA‐TDI interval did not change during follow‐up in either group, but remained longer in the recurrence group. Conclusions: The PA‐TDI interval may be useful for predicting post‐ablation AF recurrences. The patterns of time‐course changes in LAV, LVEF, and TACT differ, but the effects of ablation were better in patients without AF recurrence after ablation.